On Some Obvious Oxymorons - Malay, Armando S. (Kasarinlan: Philippine Journal of Third World Studies; Vol 10 No 2 (1994): Rethinking the State and the Economy 2, 2008)
Nongovernmental organizations and people’s organizations are just the latest newcomers to the world of ‘actually-existing’ civil society and, as they are currently constituted, are atypical elements at that. They are nothing but the same ‘civic’ or ‘voluntary associations’ that flourished in the Western democracies, dressed up in modern garb and with a hint of leftist rhetoric thrown in for good measure. Taking off from the basically correct premises that (1) the dominant ideas of a given period are the ideas of the ruling class and (2) the bourgeoisie’s conquest of state power was preceded by its domination of the civil society that was coeval with its ascendancy, the partisans of the ‘nongovernmental organizations + people’s organizations = civil society’ have stumbled upon the feebleminded notion of building a preconceived apparatus for the reproduction of ruling-class values and belief systems that will hopefully hook up somewhere in time with the postcapitalist society in gestation. However, there is no way to predict how a future hegemony will behave. Also, in reducing itself to a self-defined role of ‘monitoring and criticizing’ the government, so-called civil society does little to advance its ‘progressive’ aims, appearing instead to be a nonthreatening ally of those in power, as illustrated by the relationship between the Ramos administration and ‘civil society.’